2003
DOI: 10.1111/j.1442-2050.2003.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux before and after Helicobacter pylori eradication. a prospective study using ambulatory 24-h esophageal pH monitoring

Abstract: The aim of this study was to assess prevalence of GERD before and after Helicobacter pylori (HP) eradication utilizing 24-h esophageal pH/manometry studies. Helicobacter pylori status was confirmed by the Campylobacter like organism test. Those testing positive underwent 24-h pH/manometry followed by HP eradication therapy and urea breath test. Patients were followed up at 6 months and then at 1 year when they underwent a repeat 24-h pH/manometry. Twenty patients, 10 with non-ulcer dyspepsia (NUD) and 10 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…The prevalence of H. pylori and PUD in our center has likewise declined significantly over the past decade, 27 with a concomitant increase in EE prevalence as seen in this study. However, the relationship between EE and H. pylori appears to be purely incidental as recent reports have disproved any real associations between the two 28,29 …”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of H. pylori and PUD in our center has likewise declined significantly over the past decade, 27 with a concomitant increase in EE prevalence as seen in this study. However, the relationship between EE and H. pylori appears to be purely incidental as recent reports have disproved any real associations between the two 28,29 …”
Section: Discussionmentioning
confidence: 95%
“…Verma et al 24 found no significant correlation between the motility indexes and esophageal acid exposure in patients with GERD after eradication. Guliter and Kandilci studied 18 adult patients with GERD and Hp-gastritis using 24-hour pH-metry and static esophageal manometry.…”
Section: Discussionmentioning
confidence: 95%
“…Causative factors of GERD are considered to include reduced peristaltic activities of the esophagus and stomach, relaxation of the LES muscle, increased abdominal pressure, increased gastric acid secretion, and increased food intake 1–7 . Although there have been several studies on the gastric motility in GERD patients using EGG, 2,15–19 gastric motility has not been evaluated according to the severity of GERD or the presence of hiatal hernia.…”
Section: Discussionmentioning
confidence: 99%
“…was reduced in EGG in the GERD patients regardless of the Los Angeles grade, and a reduction in the motility of the gastrointestinal tract alone was considered to suggest GERD even in patients with no endoscopic abnormality in the upper gastrointestinal tract. Also, while the primary symptoms of GERD are heartburn and acid belching, symptoms similar to those of angina pectoris such as generalized chest pain, symptoms suggestive of respiratory disorders such as bronchial asthma and chronic cough, and otolaryngological disease‐like symptoms such as pharyngeal discomfort and hoarseness may also be caused by GERD 1–7 . EGG findings are considered to be useful for the diagnosis in such cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation